Combined 3DISCO clearing method, retrograde tracer and ultramicroscopy to map corneal neurons in a whole adult mouse trigeminal ganglion. (October 2015) - Launay, Pierre-Serge; Godefroy, David; Khabou, Hanen; Rostene, William; Sahel, Jose-Alain; Baudouin, Christophe; Melik Parsadaniantz, Stéphane; Reaux-Le Goazigo, Annabelle
Abstract: Tissue clearing and subsequent imaging of intact transparent tissues have provided an innovative way to analyze anatomical pathways in the nervous system. In this study, we combined a recent 3-dimensional imaging of solvent cleared organ (3DISCO) procedure, light-sheet microscopy, fluorescent retrograde tracer, and Imaris software to 3D map corneal sensory neurons within a whole adult mouse trigeminal ganglion (TG). We first established the optimized steps to easily and rapidly clear a fixed TG. We found that the 3DISCO procedure gave excellent results and took less than 3 h to clear the TG. In a second set of experiments, a retrograde tracer (cholera toxin B Alexa 594-conjugated) was applied to de-epithelialized cornea to retrograde-labeled corneal sensory neurons. Two days later, TGs were cleared by the 3DISCO method and serial imaging was performed using light-sheet ultramicroscopic technology. High-resolution images of labeled neurons can be easily and rapidly obtained from a 3D reconstructed whole mouse TG. We then provided a 3D reconstruction of corneal afferent neurons and analyzed their precise localization in the TG. Thus, we showed that neurons supplying corneal sensory innervation exhibit a highly specific limited dorsomedial localization within the TG. We report that our combined method offers the possibility to perform manual (on 20 μm sections) and automated (on 3D reconstructed TG) counting of labeled cells in a cleared mouse TG. To conclude, we illustrate that the combination of the 3DISCO clearing method with light-sheet microscopy, retrograde tracer, and automatic counting represents a rapid and reliable method to analyze a subpopulation of neurons within the peripheral and central nervous system. Graphical abstract: Highlights: 3DISCO method: a rapid, reliable method for clearing adult mouse trigeminal ganglion. Ultramicroscopic images of cleared ganglion containing retrogradely labelled neurons. 3D reconstruction of the distribution of corneal neurons. Automated counting of corneal neurons.